SYNCHRONIZING CONTROL OF EXTREMA REMOTE STATES - Stanovsky, A. L.; Lysenko, T. V.; Nosenko, T. I.; Lysenko, E. V. (Radio Electronics, Computer Science, Control, 2024)
A concept of «event» is defined in synchronizing control theory as nominal condition. Classification of events is maid. A method of a neuron grid extrapolation of discrete numerical temporal trends based on trend value replacement in nodal points by interpolation polynom derivative in the same points is suggested.